Drugs and development: the global impact of drug use and trafficking on social and economic development. - Singer, Merrill (The International journal on drug policy, 2008)
Locating development efforts within the context of globalism and global drug capitalism, this article examines the significant health and social impact both legal and illegal drugs have on international development efforts. The paper takes on an issue that is generally overlooked in the development debate and is not much addressed in the current international development standard, the Millennium Development Goals, and yet is one that places serious constraints on the ability of underdeveloped nations to achieve improvement. The relationship between psychotropic or "mind/mood altering" drugs and sustainable development is rooted in the contribution that the legal and illegal drug trade makes to a set of barriers to development, including: (1) interpersonal crime and community violence; (2) the corruption of public servants and the disintegration of social institutions; (3) the emergence of new or enhanced health problems; (4) the lowering of worker productivity; (5) the ensnarement of youth in drug distribution and away from productive education or employment; (6) the skewing of economies to drug production and money laundering. The paper emphasizes the need for new approaches for diminishing the burden placed by drugs on development.
Keywords: Capitalism; Crime; Developing Countries; Drug and Narcotic Control; Drug Industry; Educational Status; Efficiency; Employment; Fraud; Health; Humans; Poverty; Psychotropic Drugs; Smoking; Social Change; Street Drugs; Substance-Related Disorders; Tobacco Use Disorder; Violence; World Health